(untitled) (Bangladesh Journal of Pharmacology, 2015)
Extracellular pigment from the forest soil Streptomyces sp SFA5 was produced by submerged fermentation using yeast extract malt extract broth. Crude pigment from the medium was extracted using ethyl acetate. Antitubercular activity of the pigment was tested against M. tuberculosis H37Rv by microplate alamar blue assay and luciferase reporter phage assay. The pigment was also tested for inhibitory activity against M. tuberculosis lysine aminotransferase by colorimetric method. In both microplate alamar blue and luciferase reporter phage assay, the crude pigment showed activity against M. tuberculosis H37Rv at 125 and 250 µg/mL concentration, respectively. The M. tuberculosis lysine aminotransferase was inhibited at the IC50 value of 4.5 µg/mL concentration.